Оруженосец Кашка - Крапивин Владислав Петрович (Детская литература, 2007)
Экземпляры: (20210408) / Инвентарный номер: 33721 / Цена: 76.30 / Сис.шифр: Р2 / Авт.знак: К 78 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6